Efektivitas Mediasi Penal Pada Proses Penyidikan Kasus Kekerasan Perspektif Restorative Justice (Studi di Kepolisian Resor Bojonegoro) - Ameilia Herpina Denovita; Hervina Puspitosari (Yustisia Tirtayasa: Jurnal Tugas Akhir, 2022)
This research aims to determine the implementation of penal mediation for violent crimes against the investigation process at the Bojonegoro Police, the effectiveness of the penal media in realizing the principle of restorative justice at the Bojonegoro Police in reducing violent crimes, as well as discussing issues related to the application of penal mediation in violent cases at the Resort Police. Bojonegoro, and the second sub-chapter discusses efforts to overcome obstacles to the implementation of effective mediation. This type of legal research is empirical. Sources of data obtained in this study using primary, secondary, and tertiary legal materials. The results of this study can be said that the penal mediation carried out on cases of violence was not successful. The factors that hinder the implementation of mediation are that the party who is the victim of the case remains to be continued because it is harmed, and the victim does not want an attempt to harm the losses obtained from the perpetrator's actions and only wants to continue the case through the litigation stage so that the perpetrator of the punishment is equivalent to the act.. Efforts to overcome these obstacles are through penal mediation accompanied by the Bojonegoro Police as law enforcement officers who act as mediators who are neutral and protect the community, and the need for third party assistance such as experienced mediators, families of litigants, and community leaders who was at the scene of the incident.